Montessori Education and Cognitive Skill Development in Preschool Students: A Quantitative Systematic Review - Mujahidah Faizah; Ruqoyyah Fitri; Yes Matheos Lasarus Malaikosa; Andi Kristanto; Nurul Istighfaroh; Mohammad Syaikhul Haq (Lembaga Teewan Journal Solutions, 2026)
This systematic review examines the effects of Montessori education on cognitive skills in preschool and kindergarten children. The review synthesizes quantitative empirical studies conducted in formal Montessori educational settings and published between 2015 and 2025. Ten studies met the inclusion criteria and were analyzed using a narrative synthesis approach with attention to methodological quality and statistical rigor. Overall, the findings indicate that Montessori education is associated with significant improvements in multiple cognitive domains, including executive functioning, early literacy, mathematical reasoning, creativity, and fine motor skills, when compared with conventional educational programs. Studies employing randomized or lottery-based admission designs reported medium to large effect sizes, providing stronger support for causal interpretations. Several studies also suggest cumulative or delayed cognitive benefits and indicate that Montessori education may offer compensatory advantages for children from socioeconomically disadvantaged backgrounds. Despite heterogeneity in research designs and outcome measures that limits formal meta-analytic synthesis, this review provides robust quantitative evidence supporting the effectiveness of Montessori education in promoting early cognitive development.